Association of dietary intake with a risk factor of atherosclerosis – abdominal obesity in men of Novosibirsk - A. K. Kuntsevich; S. V. Mustafina; E. G. Verevkin; D. V. Denisova; S. K. Malyutina; G. I. Simonova (Атеросклероз, 2015)
Aim. To evaluate association between the nutrition habits and abdominal obesity in cross-sectional population study among men 45-69 years in Novosibirsk.